γ-Al2O3-supported XMo6 Anderson Heteropolyoxomolybdates: Adsorption Studies for X = TeVI, AlIII, CoIII, CrIII and NiII by DR Spectroscopy and TPR Analysis - Cabello, Carmen Ines (2000)
The support–overlayer adsorptive interactions, generated when solutions of Anderson heteropolyoxomolybdates were supported as a monolayer on γ-Al2O3 by means of the equilibrium adsorption method, were studied by XRD analysis, DR spectroscopy, electron microscopy (SEM–EDAX) and TPR methods. The adsorption isotherms and corresponding adsorption parameters (number of active sites and adsorption constants) of the γ-Al2O3-supported ammonium heptamolybdate were obtained and discussed. The following sequence of adsorption strength was suggested: CoMo6 > CrMo6 > TeMo6 ~ AlMo6 > NiMo6. The effectiveness of the TPR technique as a tool for elucidating interaction effects was clearly demonstrated. The formation of a γ-Al2O3-supported Te–Mo mixed valence oxide appears to provide new and interesting catalytic possibilities.